Consummatory successive negative contrast in Mongolian gerbil (Meriones unguiculatus) (2016)
Successive Negative Contrast (SNC) is a phenomenon in which there is a sharp decrease in the rate of reinforced behavior immediately after a sudden reduction in quality or quantity of a habitual reinforcer. This phenomenon has become a solid experimental paradigm for the study of frustration in mammals but it has not been reported to date in the Mongolian gerbil (Meriones unguiculatus). This species is monogamous and biparental, and these differential characteristics make it interesting for comparative analysis. This work includes modifications to the SNC paradigm for this species, assessing its response to sudden changes in positive reinforcement and its differences by sex. In the first phase of the experiment, a multiple choice test was used to identify the preferred reinforcer for the species (sesame paste). After the selection of the primary incentive, the contrast procedure was carried out by presenting sesame paste in the pre-shift phase and LabDiet, Laboratory Rodent Diet, food during post-shift one. A repeated measures ANOVA of showed a significant reduction of consummatory behavior in the experimental group when compared with the control group. No differences were observed by sex. These data expand the possibility of using gerbils in the comparative study of the relationship between learning and emotion in mammals, both in behavioral and in neurobiological levels.